Apex realty / Irfan Danish Mohd Salleh - Mohd Salleh, Irfan Danish (Universiti Teknologi MARA, Kedah, 2025)
The project that we do is to rebrand this company that my client is SUE PROPERTIES. The founder of SUE PROPERTIES is Nur Suhaini Binti Ismail, and the target audience is adults (average age is 25 years old and above) . The agent's motivation is to assist a customer in finding a suitable home for their family. When we rebrand this company from SUE PROPERTIES to APEX REALTY, that means the highest achievement in real estate. And we also create one tagline for this company: Your Trusted Home Partner. This implies that customers can trust us with all aspects of real estate, including their homes. Next, they are offering three services to our customers: selling, renting, and buying. All the services have their own benefits that they give to our customers. Additionally, we are enhancing their colour design to make it more appealing, which will encourage customers to learn more about our services.This company also maintains a collection of corporate stationery items. Then the stationery item has a business card, envelope, letterhead, form, and corporate folder, as well as a brochure about the company. We also produce merchandise for our customers and agents. Merchandise that we create is a mug, pen, umbrella, tumbler, and laser card. Next for our agents, we also have uniforms, like corporate and T-shirt colors. We do all this because we want our clients to be informed about real estate and help them find a house they like.